The reemerging and outbreak of genotypes 4 and 5 of Japanese encephalitis virus - Zhang, Weijia; Yin, Qikai; Wang, Huanyu; Liang, Guodong (Frontiers in Cellular and Infection Microbiology, 2023)
The Japanese encephalitis virus (JEV) is classified into five distinct genotypes, with genotypes 1 and 3 historically showing higher activity. These genotypes are the primary agents of viral encephalitis in the Asian continent. Genotypes 4 and 5 have remained silent in low-latitude tropical regions since their discovery. From 2009, the hidden genotype 5 suddenly emerged simultaneously in mosquitoes from the Tibetan region of China and those from South Korea in East Asia. The detection of genotype 5 of JEV in these mosquitoes was associated with cases of viral encephalitis in the local population. Similarly, in 2022, the long-silent genotype 4 of JEV emerged in Australia, resulting in a local outbreak of viral encephalitis that primarily affected adults and caused fatalities. The emergence and outbreaks of genotypes 4 and 5 of JEV present new challenges for the prevention and control of Japanese encephalitis (JE). This study not only analyzes the recent emergence of these new genotypes but also discusses their implications in the development of JE vaccines and laboratory tests for newly emerging JEV infections.